KESESUAIAN IKLIM TERHADAP PERTUMBUHAN TANAMAN THE CLIMATE SUITABILITY FOR PLANT'S GROWTH - Dewi, Nur Kusuma (Universitas Wahid Hasyim, 2005)
This studies purposed to analyze climate classification which is used in Indonesia commonly and the suitability each climate type for plant's growth. The climate classification can be made by using only one climate substance or more. The prominent classifications in Indonesia are Schimdt ± Ferguson system and Oldeman system. Schmidt ± Ferguson classification system appropiate to wooded plant / plantation and forest growth, while Oldeman system appropiate to seasonal plants like rice or dry season crops. The suitable climate is one of the optimal production determined factors. Keywords : Schimdt = Ferguson, Oldeman , Wooded plants, Seasonal plants